Performa Wasit Sepak Bola Ditinjau dari Level Kebugaran, Pemahaman Peraturan dan Anxiety Pra Pertandingan - Bandan Naizi Nugraha; Herman Subarjah; Septian Williyanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to examine the effects of physical fitness level, understanding of the Laws of the Game, and anxiety on the performance of football referees, both individually and simultaneously. This study employed a quantitative approach using an ex post facto design and a correlational method. The participants consisted of 34 active football referees registered with the Bandung City Football Association (Askot PSSI Bandung City), selected through purposive sampling. The research instruments included the Fitness Test for Referees Men, the Laws of the Game Knowledge Test, the Competitive State Anxiety Inventory-2 Revised (CSAI-2R), and the Assessment of the Referee's Performance. Data were analyzed using multiple linear regression. The results indicated that, simultaneously, the three independent variables had a significant effect on referee performance (F = 7.317; Sig. = 0.001), accounting for 42.3% of the variance (R² = 0.423). Partially, physical fitness level (t = -3.955; Sig. = 0.000) and pre match anxiety (t = -3.493; Sig. = 0.002) had significant effects on referee performance, whereas understanding of the Laws of the Game did not have a significant effect (t = -0.869; Sig. = 0.392). These findings indicate that referee performance is influenced by a multidimensional interaction between physical and psychological factors. It can be concluded that referee development programs should be designed holistically by emphasizing improvements in physical fitness, strengthening knowledge of the Laws of the Game through simulation based training, and enhancing anxiety management and mental resilience skills. Keywords: Football, Laws Of The Game, Physical Fitness, Pre Match Anxiety, Referee Performance